PELATIHAN PEMBUATAN MEDIA PEMBELAJARAN DARING APRESIASI SENI BERBASIS ANDROID SMARTPHONE: PELATIHAN PEMBUATAN MEDIA PEMBELAJARAN DARING APRESIASI SENI BERBASIS ANDROID SMARTPHONE - Esterica Yunianti; Edi Kurniadi (Lembaga Penelitian dan Pengabdian Masyarakat, 2022)
This service aims to provide knowledge and practice of making online art appreciation learning media during the COVID-19 pandemic based on Android smartphones. The use of android smartphones as a tool for making learning media is based on the consideration that android smartphones have increasingly diverse uses because they are supported by the availability of various applications. The training was conducted for middle school art and culture teachers in Karanganyar. Implementation of the training using the lecture method to convey theoretical material about learning media, discussions to determine the concept of learning media to be made, and assistance in making learning media based on Android smartphones. The results of the training in the form of learning media are then carried out field trials to determine the success and shortcomings. After the learning media is improved, the learning media can be used in online art appreciation learning. Keywords: learning media, art appreciation, android smartphone